The effect of asset quality, profit and loss sharing on Sharia Banking Liquidity in Indonesia - Anggraeni, Anggraeni; Berniz, Yulis Maulida (Technium Social Sciences Journal, 2022)
This study aims to determine the effect of asset quality variables (Non-Performing Financing), Profit and Loss Sharing (profit-loss sharing investment and profit-sharing investment account), capital adequacy ratio, bank size and return on assets on Islamic banking liquidity in Indonesia. The analysis was conducted using a sample of 7 Islamic commercial banks from the period March 2015 to December 2019. This study uses 2 multiple regression models of panel data with the results showing that Non-Performing Financing, profit- loss sharing investment, bank size, affect the liquidity of Islamic banks. , then for-profit sharing investment account, capital adequacy ratio, return on assets, does not affect the liquidity of Islamic banks.